Calcium and Magnesium in Ilam Drinking Water Sources during 2009-2013 using Geographic Information System (GIS) - Zabihollah Yousefi; Farzad Kazemi; Reza Ali Mohammadpour (Iranian Journal of Health, Safety and Environment, 2017)
Physicochemical quality of water from the acceptability point of view is essential for consumers; protecting the health of consumers and maintenance of water supply systems. The aim of this study is to determine temporal and spatial variations of Calcium and Magnesium in Ilam drinking water sources using the GIS system. This cross-sectional study was conducted on 20 drinking water sources in Ilam city and the 5 years results by water and wastewater company archive GIS software version 3.9 were analyzed via SPSS version 16 as well as one-way variance analysis. Water and wastewater sampling and measurement were conducted in order to verify the data by researchers according to standard methods. Based on interpolation map, the maximum calcium and magnesium contents are related to western and central regions. ANOVA test showed that there no a significant difference between the mean calcium variable verification test in summer during 2009-2013 and at 95% level. (P=0.760>0.05). The one-way analysis of variance showed that there is a significant difference between the average magnesium variable in summer during 2013-2009 years and the verification test at 95% level. (P=0.019